The Influence of Digital Marketing and Brand Image on Consumer Purchase Interest in Ashiaapfood Instant Food Products - Desfitriady; Wandi Diwana (International Journal of Scientific Multidisciplinary Research, 2024)
The purpose of this study is to ascertain how consumer interest in purchasing Ashiaapfood quick food products is influenced by digital marketing and brand image. This study uses an associative and descriptive technique approach and is quantitative in nature. 535,800 TikTok users who follow ASHIAAAP Food were the study's population, and 100 respondents made up the sample. In addition to using the multiple linear regression analysis approach, this analysis additionally tests the research instrument's validity and reliability. The study findings indicate that brand image and digital marketing factors have a simultaneous and partial impact on purchase interest. According to this research, ASHIAAAP Food can assess its brand image and digital marketing on TikTok social media to pique consumers' interest in making a purchase from consumers of ASHIAAAP Food goods. According to this study, brand image has a 67.85% influence on purchasing interest, but digital marketing has a 16.05% influence. Eighty-three percent of purchase interest is impacted by brand image and digital marketing, with the remaining seventeen percent coming from other factors not covered in this study